Performance of a photothermal detector with turbid liquids - Hodgkinson, Jane; Johnson, Mark; Dakin, John P. (Optical Society of America, 2005)
A closed-cell photothermal detector for aqueous analytes has been evaluated at 254nm and 678nm. The detector used a water meniscus as a pressure sensor, whose periodic deflection was measured using a low finesse optical fibre Fabry-Perot interferometer. Performance was compared with a commercial diode-array spectrometer and found to be similar for absorption measurements in non-turbid samples, but the results were affected up to 60 times less by scattered light. Finally the photothermal cell was converted into an integrating cavity using ceramic inserts, showing freedom from scattering related errors at 678nm but a degradation in performance at 254nm.